Analysis Of Marketing Strategy In Students Face Masks Business Folta Repper: Folium Tamarin Rice Paper - Marlan Siregar; Sri Lestari; Aulia Hafizah Lubis (JASc (Journal of Agribusiness Sciences), 2019)
In this era people prefer to use instant products. We found this problem during the survey for market opportunities. In addition there are several other problems such as: (1) The length of time in treatment. (2) Difficulty using the product. (3) Solid activity making it difficult to take the time to treat your face. We are here to solve this problem by creating a Folta Reper (Folium Tamarin Rice Paper) product. This product is an instant transparent mask that can be used anytime and anywhere by women and men. Using FOLTA REPER will not interfere with other activities. Made from natural ingredients: Sour leaves, honey and Rice Paper. The contents of FOLIUM TAMARIN RICE PAPER are: vitamin C, vitamin A, vitamin B1, vitamin B, vitamin B12 and vitamin D. The benefits of removing pimples, making faces brighter, preventing premature aging, lifting dead cells, lifting dead cells , whitening the face, cooling the skin, spreading the face minimizes pores, smooths the skin and removes smallpox scars on the face. The purpose of this study is to study and analyze "marketing strategies in marketing in the Folta Reper Student Mask business, so that they can find solutions to the problems faced. This study uses an analytical descriptive method by classifying strengths, weaknesses, opportunities and threats and establishing marketing strategies that match the marketing mix. The conclusion of this study is the identification of strengths, weaknesses, opportunities and threats possessed by the product and the intensification of several business strategies through a marketing mix approach.